Ist die Expression des GP88-Proteins (Progranulin) ein klinisch relevanter Prognosefaktor für Prostatakarzinompatienten? - Taubert, Helge; Eckstein, Markus (Journal für Urologie und Urogynäkologie, 2021)
Progranulin (GP88), an autocrine growth factor, has been recognized as a biomarker in several tumor entities. GP88 can be detected in the tumor tissue and serum of patients, which enables its detection in a minimally invasive (liquid biopsy) test. In prostate cancer (PCa), studies on this marker have been only preliminary as yet. The authors’ own studies analyzed the protein level of GP88 protein in the serum (enzyme-linked immunosorbent assay) and tumor tissue (immunohistochemistry) in two PCa patient cohorts separately. The detection of increased GP88 protein in both tumor tissue and serum appeared to be a negative prognostic biomarker. Interestingly, this result related only to younger PCa patients. Further studies are needed to confirm these results and to estimate the eligibility of GP88 for diagnosis and treatment monitoring in PCa patients.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Biomarker; Immunohistochemistry; Prognosis; Progranulin; Prostate cancer